2009
DOI: 10.1017/s0022112009006879
|View full text |Cite
|
Sign up to set email alerts
|

Cylinders with square cross-section: wake instabilities with incidence angle variation

Abstract: The wakes behind square cylinders with variation in incidence angle are computed over a range of Reynolds numbers to elucidate the three-dimensional stability and dynamics up to a Reynolds number of Re = 300, based on the projected height of the inclined square cylinder. Three-dimensional instability modes are predicted and computed using a linear stability analysis technique and three-dimensional simulations, respectively. Depending on the incidence angle, the flow is found to transition to three-dimensional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
124
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(141 citation statements)
references
References 45 publications
16
124
1
Order By: Relevance
“…Breaking this symmetry can change the nature of three-dimensional bifurcations that are possible from the two-dimensional basic state. Of particular significance in relation to the present work is the fact that subharmonic modes which can arise in systems with broken Z 2 symmetry (as shown by Sheard et al 2003, Carmo et al 2008, Sheard, Fitzgerald & Ryan 2009, respectively, for wakes of rings, of a staggered pair of circular cylinders, and of a rotated square cylinder) are suppressed as generic bifurcations in symmetric systems. This outcome is a direct consequence of Z 2 spatio-temporal symmetry, as originally explained for simple systems by Swift & Wiesenfeld (1984), and in depth for Z 2 ×O(2) systems by Marques et al (2004).…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…Breaking this symmetry can change the nature of three-dimensional bifurcations that are possible from the two-dimensional basic state. Of particular significance in relation to the present work is the fact that subharmonic modes which can arise in systems with broken Z 2 symmetry (as shown by Sheard et al 2003, Carmo et al 2008, Sheard, Fitzgerald & Ryan 2009, respectively, for wakes of rings, of a staggered pair of circular cylinders, and of a rotated square cylinder) are suppressed as generic bifurcations in symmetric systems. This outcome is a direct consequence of Z 2 spatio-temporal symmetry, as originally explained for simple systems by Swift & Wiesenfeld (1984), and in depth for Z 2 ×O(2) systems by Marques et al (2004).…”
Section: Introductionmentioning
confidence: 75%
“…Blackburn & Lopez 2003b;Sheard, Thompson & Hourigan 2004;Blackburn et al 2005;Sheard et al 2009). Especially in Cartesian geometries, this may seem a reasonable expedient since the spanwise spectrum is continuous in the infinite-geometry case, although examples in which this issue was tackled by expanding the extent of the discrete spectrum are provided by Henderson (1997) and Avila et al (2007).…”
Section: Nonlinear Mixed Modesmentioning
confidence: 99%
“…Considering the experimental uncertainty, it can be said that the results presented above matches the previous observations. Furthermore, Sheard et al 31 mentioned that a spanwise wavelength of 2.6 diameters for the Mode-C in square cylinders. However, in stability calculations of the flow around bluff rings, Sheard et al 8 found a maximum growth rate for Mode-C instability for spanwise wavelengths between 1.6D and 1.7D.…”
Section: B Streamwise Vorticesmentioning
confidence: 99%
“…An example of such an application is the design of buildings. Most experimental [1,2] and numerical studies [2][3][4][5][6][7][8][9] concerning the external flow past a stationary square cylinder have been carried out at moderate to high Reynolds numbers. In this regime, the flow is unsteady.…”
Section: Introductionmentioning
confidence: 99%